Advanced Computational Methodologies Used in the Discovery of New Natural Anticancer Compounds - Chavda, Vivek P.; Ertas, Yavuz Nuri; Walhekar, Vinayak; Modh, Dharti; Doshi, Avani; Shah, Nirav; Anand, Krishna; Chhabria, Mahesh (Frontiers in Pharmacology, 2021)
Natural compounds have been widely investigated for their programmed necrosis impending for more than half an era. Natural compounds used as concoctions or concentrated plant extracts without isolation of active moieties are the conventional method for the screening of the plant for its desired pharmacological activity. Modern medicine relies on the isolation and purification of complicated one or two active and isomeric compounds. Extraordinary chemical diversity, large natural moieties convert into small potent molecules which significantly play an important role in multi-target pharmacology. With remarkable and tremendous advancement, carrying natural compounds for clinical use and discovery of new chemical entity (NCE) is a considerable challenge to continue forward. This mini-review summarizes the key advancements in natural anticancer compounds; computer-assisted/fragment-based structural elucidation and a multi-target approach for the exploration of natural compounds.